A novel passive filtration system for splash-lubricated gearboxes: Part 1. (October 2020) - Yang, Chi; Abanteriba, Sylvester; Becker, Andrew
Splash-lubricated gearboxes are widely used in many industries. Contaminant removal systems are rarely employed in splash-lubricated gearboxes, such as some gearboxes are used in helicopters and mining machines. The maintenance of lubrication systems in those machines relies on periodic onsite inspection and lubricant change. However, wear debris generated during operation will suspend in lubricant and cause damage to contacting surfaces of gearbox's components. In this first part of a two-part paper, a novel light-weight passive filtration system that utilises gravitational sedimentation and shape memory alloys is presented for unfiltered splash-lubricated gearboxes. A predictive model is developed for the estimation of flake-like wear particles' settling behavior in the lubricant. Experiments based on a simplified test rig are also conducted to validate the theoretical results. This mathematical model can also be used to elucidate the impact of sedimentation time of wear particles on the cleanliness of the lubricant after the installation of passive filtration system.